Accuracy of [18Fluorine]-Fluoro-2-Deoxy-d-Glucose Positron Emission Tomography-Computed Tomography Response Assessment Following (Chemo)radiotherapy for Locally Advanced Laryngeal/Hypopharyngeal Carcinoma. (13th June 2017) - Slevin, Finbar; Ermiş, Ekin; Vaidyanathan, Sriram; Sen, Mehmet; Scarsbrook, Andrew F; Prestwich, Robin JD
Introduction: The accuracy of response assessment positron emission tomography (PET)-computed tomography (CT) following radiotherapy with or without chemotherapy for laryngeal/hypopharyngeal squamous cell carcinoma is uncertain. Methods: In all, 35 patients with laryngeal or hypopharyngeal squamous cell carcinoma who were treated between 2009 and 2014 with (chemo)radiotherapy were identified. The accuracy of response assessment PET-CT was made by correlation with clinical follow-up and pathological findings. Results: Of the 35 patients, 20 (57%) had an overall complete metabolic response. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for response assessment [ 18 Fluorine]-fluoro-2-deoxy-d -glucose (FDG) PET-CT for primary and nodal sites, respectively, were 100%, 73%, 46%, and 100% and 83%, 95%, 83%, and 95%. Conclusions: Response assessment FDG PET-CT following (chemo)radiotherapy for laryngeal and hypopharyngeal carcinomas has a high NPV for both primary site and lymph nodes and can be used to guide treatment decisions. The PPV of residual FDG uptake at the primary tumour site is limited and requires examination and biopsy confirmation.